One-dimensional approximation of heat transfer in flashlamp-assisted automated tape placement - Danezis, Anastasios; Williams, David; Skordos, Alexandros A. (Sage, 2023)
A computationally efficient heat transfer simulation of flashlamp-assisted automated tape placement (ATP) is put forward in this work. The simulation combines distinct 1D finite element models representing the tow, the deposited material, and the resulting stack with appropriate transfer of temperature information to ensure field continuity. Direct comparison against a validated 2D model of ATP shows good agreement in the irradiation region, underneath and beyond the roller vicinity with errors up to 14°C. The combined solution of 1D models requires only 1-2% of the computational effort needed for an equivalent 2D analysis without compromising results resolution, whilst it is better suited for providing the full material temperature history throughout consecutive processing cycles. The accuracy and fast computation render this method appealing for studies which require an iterative execution of the model in a practical timeframe such as in optimisation schemes, inverse solutions, training of surrogate models and stochastic simulation.
Keywords: Finite element analysis; Process modelling; Thermoplastics; Tape placement; Pulsed heating